Effects of different metabolic states and surgical models on glucose metabolism and secretion of ileal L-cell peptides: protocol for a cross-sectional study. Issue 3 (14th March 2016) - Celik, Alper; Dixon, John B; Pouwels, Sjaak; Celik, Bahri Onur; Karaca, Fatih Can; Gupta, Adarsh; Santoro, Sergio; Ugale, Surendra
Abstract : Introduction: Obesity and type 2 diabetes mellitus are increasing worldwide, reaching pandemic proportions. The understanding of the role of functional restriction and gut hormones can be a beneficial tool in treating obesity and diabetes. However, the exact hormonal profiles in different metabolic states and surgical models are not known. Methods and analysis: The HIPER-1 Study is a single-centre cross-sectional study in which 240 patients (in different metabolic states and surgical models) will receive an oral mixed-meal tolerance test (OMTT). At baseline and after 30, 60 and 120 min, peptide YY and glucagon-like peptide 1 levels and glucose and insulin sensitivity will be measured. The primary end point of the study will be the area under the glucagon-like peptide 1 and peptide YY curves after the OMTT. Secondary study end points will include examination of the difference in plasma levels of the distal ileal hormones in subjects with various health statuses and in patients who have been treated with different surgical techniques. Ethics and dissemination: An independent ethics committee, the Institutional Review Board of Istanbul Sisli Kolan International Hospital, Turkey, has approved the study protocol. Dissemination will occur via publication, national and international conference presentations, and exchanges with regional, provincial and national stakeholders. Trial registration number: NCT02532829; Pre-results.